2010
DOI: 10.1038/sc.2010.66
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and predictors of pressure ulcers during primary in-patient spinal cord injury rehabilitation

Abstract: Study design: Multicenter prospective cohort study. Objectives: To determine the occurrence and predictors for pressure ulcers in patients with spinal cord injury (SCI) during primary in-patient rehabilitation. Setting: Eight Dutch rehabilitation centres with specialized SCI units. Methods: The occurrence, location and stage of pressure ulcers were registered between admission and start of functional rehabilitation (called acute rehabilitation phase) and between start of functional rehabilitation and discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 17 publications
5
72
2
16
Order By: Relevance
“…21 Several studies have tried to give an overview about the circumstances when HAPUs occur 1,3 by doing retrospective analysis over periods of 3 months or divide occurrences in different rehabilitation phases. By knowing and confirming the influence of length of stay, 4,5 our daily-based observations put perspective about the influence of time on the development of HAPU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Several studies have tried to give an overview about the circumstances when HAPUs occur 1,3 by doing retrospective analysis over periods of 3 months or divide occurrences in different rehabilitation phases. By knowing and confirming the influence of length of stay, 4,5 our daily-based observations put perspective about the influence of time on the development of HAPU.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, studies in non-SCI patients showed that HAPUs occurred relatively early after admission, varying from 6.2% within 2 days of admission 9 to 12.4% within 7 days on admission to an intensive care unit. 10 On average, less severe HAPUs occurred earlier than severe HAPUs on intensive care units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated complications following SCI and their risk factors. They have illustrated the association between subject and lesion characteristics and the occurrence of complications (8,9).…”
Section: Sažetakmentioning
confidence: 99%
“…Проценат декубиталних улкуса је био 36.5% са најчешћом локализацијом на сакруму (43%), петама (19%) и исхијуму (15%). Резултати осталих студија који су се бавили локализацијом декубиталних улкуса наводе: сакрум, исхијум и пете [107][108][109]. Овакви резултати су у корелацији са нашим резултатима.…”
Section: компликације током рехабилитацијеunclassified